Development of a One-Stop Service Promotion Model for Low Vision at Cicendo Eye Hospital, Bandung - Pohan, Hani Ulfah; Sukoco, Dwi Heru; Susilawati, Susilawati (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2024)
Limited promotion does not adequately support increased community access to services. The limitations of promotion are related to promotional planning that is still not comprehensive and non-participatory. This research aims to develop a comprehensive and participatory service promotion planning model. This research used a qualitative approach with Participatory Action Research (PAR). It involved patients, families and communities, ophthalmologists, social workers, psychologists, health educators, optometrists, public relations staff and health promotion staff. The data were collected by observation, documentation study, in-depth interview and focus group discussion. Validity testing used credibility, transferability, dependability and confirmability techniques. Then it was analyzed by usingMile & Huberman model. The research findings show that this model produces a comprehensive service promotion system, and ensures the dissemination of information that is more accessible to service users thus improving service delivery. The model uses the concept of society 5.0 which includes the use of digital technology, emphasis on the balance between technology and people, continuous capacity building such as education and skills training, the use of integrated systems, data security and privacy. The model offers ease of implementation as it has five steps that are systematic and participatory. The pilot test of this model at Cicendo Eye Hospital has resulted in continuous dissemination of information utilizing audio-visual media technology and has resulted in an increase in the number of patients. The use of audio-visual media technology has proven to make it easier for people with visual disabilities to obtain information.